LARANGAN PENGASINGAN TANAH DAN PELUANG INVESTASI ASING DI INDONESIA - Sumarja, FX (Jurnal Media Hukum, 2014)
Throughout the political history, agrarian law in Indonesia recognize the prohibition of land alienation. Foreigners orÂ  foreignÂ  legalÂ  entitiesÂ  (foreignÂ  investors) wereÂ  bannedÂ  forÂ  landÂ  ownership.Â  ArgrarianÂ  FundamentalÂ  Lawsstipulates that foreigners domicile in Indonesia and foreign legal entities which have representatives in Indonesia areÂ  onlyÂ  allowedÂ  to haveÂ  landÂ  useÂ  rightsÂ  andÂ  buildingÂ  leaseÂ  rights.Â  InÂ  practice,Â  foreignersÂ  andÂ  foreignÂ  legalentities preferÂ  toÂ  acquireÂ  landÂ  ownershipÂ  rights by nominee. WhereasÂ  nomineeÂ  isÂ  illegalÂ  andÂ  hasÂ  very weak legal position. Article 16 paragraph (1) letter h junto Article 24 Argrarian Fundamental Laws open the opportunitiesfor foreign investorsÂ  in land tenure through Guna Bangun Serah rights, by positioning the ground as a means of productionÂ  ratherÂ  than as anÂ  investment. Guna Bangun SerahÂ  inÂ  Indonesia was marked by the birth ofÂ  theMinister of Finance ofÂ  the Republic of Indonesia Decree No. 470 / KMK.01Â  / 1994 on Procedures for Removal and Utilization of AssetsÂ  / Countryâs Wealth, which adoptedÂ  theÂ  âTurgutâs Formulaâ, namelyÂ  the construction and management of dams on the river Syehan Turkey.This study aims to find an alternative land ownership for foreignÂ  investors thatÂ  requireÂ  land asÂ  ingredients, consideringÂ  theÂ  limitedÂ  tenureÂ  inÂ  IndonesiaÂ  to considerÂ  theexpediencyÂ  ofÂ  justiceÂ  andÂ  legalÂ  certainty.Â  TheÂ  newÂ  paradigmÂ  is neededÂ  inÂ  attractingÂ  foreignÂ  investmentÂ  in Indonesia, in order to obtain the benefit, justice and legal certainty, through Bangun Guna Serah rights. Article 16 paragraph (1) letter h Argrarian Fundamental Laws stipulates the other rights that are not included: Properties, CultivationÂ  rights, BuildingÂ  rights,Â  TenureÂ  and RentalÂ  Rights willÂ  beÂ  establishedÂ  byÂ  law.Â  Bangun GunaÂ  Serah rights defined as rights to construct a building and / or its facilities on land that is not his own and then utilize the building andÂ  / orÂ  its facilitiesÂ  in aÂ  certain period ofÂ  time that has been agreed, asÂ  inÂ  theÂ  future theÂ  land, buildingsÂ  andÂ  / orÂ  theÂ  followingÂ  facilities will beÂ  transferedÂ  toÂ  the owner ofÂ  theÂ  land afterÂ  theÂ  term expired. Guna Bangun SerahÂ  rightsÂ  can beÂ  incorporated intoÂ  the Land Bill.